Successful use of the forced choice test for detecting concealment of semantic memory in criminal and intelligence investigations - Ashkenazi, Tzachi; Goldzweig, Gil; Vrij, Aldert; Leal, Sharon (Frontiers in Psychology, 2024)
The current study examined the validity of the forced choice test (FCT) in a forensic scenario when used to detect concealment of semantic memory (SM-FCT). We also compared the SM-FCT validity to the FCT validity in the more commonly investigated episodic memory scenario (EM-FCT). In simulating a scenario of investigating suspected members of a terror organization, 277 students were asked to deceptively deny being enrolled in a college in which they do actually study. Results indicated that the SM-FCT's validity level was within the range of the EM-FCTs' validity levels. Theoretically, the results support a cognitive-based explanation for the FCT operation mechanism.Practically, they imply that FCT can be used in criminal or intelligence investigations of suspected members of terrorist or criminal organizations or suspected perpetrators of illegal acts or acts of terrorism, in which the incriminating evidence being sought is in the realm of designated semantic memory or knowledge.